Exploiting Weak Field Gravity-Maxwell Symmetry in Superconductive Fluctuations Regime - Giovanni Alberto Ummarino (Symmetry, 2019)
We study the behaviour of a superconductor in a weak static gravitational field for temperatures slightly greater than its transition temperature (fluctuation regime). Making use of the time-dependent Ginzburg−Landau equations, we find a possible short time alteration of the static gravitational field in the vicinity of the superconductor, providing also a qualitative behaviour in the weak field condition. Finally, we compare the behaviour of various superconducting materials, investigating which parameters could enhance the gravitational field alteration.